Back Cover: Controlling Internal Pore Sizes in Bicontinuous Polymeric Nanospheres (Angew. Chem. Int. Ed. 8/2015). Issue 8 (28th January 2015) - McKenzie, Beulah E.; Friedrich, Heiner; Wirix, Maarten J. M.; de Visser, Joël F.; Monaghan, Olivia R.; Bomans, Paul H. H.; Nudelman, Fabio; Holder, Simon J.; Sommerdijk, Nico A. J. M.
<x xml:space="preserve">Abstract</x> The internal morphology of complex polymeric nanospheres was resolved by S. J. Holder, N. A. J. M. Sommerdijk et al., as reported in their Communication on page 2457 ff. They demonstrated that the internal structure can be controlled by changing the overall molecular weight and relative hydrophilic content of the composite polymer. This opens the way for using these bicontinuous polymer nanospheres in a variety of applications, such as controlled release vectors and as templates for the synthesis of inorganic and hybrid materials.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>